High resting energy expenditure, less fat-free mass, and less muscle strength in HIV-infected children: a matched, cross-sectional study - Franco-Oliva, Andrea; Pinzón-Navarro, Beatriz Adriana; Martínez-Soto-Holguín, Martha C.; León-Lara, Ximena; Ordoñez-Ortega, Javier; Pardo-Gutiérrez, Ana Laura; Guevara-Cruz, Martha; Avila-Nava, Azalia; García-Guzmán, Alda Daniela; Guevara-Pedraza, Laura; Medina-Vera, Isabel (Frontiers in Nutrition, 2023)
Background and aims Many improvements have been made in the treatment of human immunodeficiency virus (HIV) in pediatric patients; however, challenges remain in terms of achieving normal growth, body composition, and metabolism during treatment, etc. Current nutritional recommendations are based on studies performed in adults, with limited data on the HIV-infected pediatric population. Therefore, this study aimed to compare the resting energy expenditure (REE) of asymptomatic HIV-infected pediatric patients with healthy counterparts and to compare body composition, dietary intake, and physical activity between the two groups. Methods This was a cross-sectional study of asymptomatic HIV-infected children who were receiving antiretroviral therapy; the infected group was compared with the uninfected group, matched by age (± 6 months), sex, and body mass index (± 0.5 z-score). Participants were recruited between 2021 and 2022, as outpatients. In both groups, REE was determined by indirect calorimetry and body composition by bioelectrical impedance analysis and hand strength, measured using a hydraulic hand dynamometer. Results Seventy-eight participants were enrolled, where n = 39 HIV-infected children and n = 39 controls, with a mean age of 11.6 ± 3.4 years old. REE was significantly higher in the HIV group (1254.4 ± 334.7 kcal/day vs. 1124.7 ± 321 kcal/day, p = 0.013) than in the control group. Fat-free mass (FFM) was lower in the HIV group (28.2 ± 10.5 kg vs. 32 ± 11.2 kg, p = 0.001); this trend continued when the index skeletal muscle was evaluated (7.2 ± 1.2 vs. 7.6 ± 1.5, p = 0.04). The strength of the dominant hand was also lower in the HIV group (12 (8–18) kg vs. 20 (10.5–26) kg, p < 0.0001). Conclusions Children with asymptomatic HIV infection have higher REE than their uninfected peers. They also present decreased FFM, skeletal muscle mass index, and muscle strength. These parameters should be considered during nutritional assessment in this population to have a favorable impact on nutritional status and growth.